1999
DOI: 10.1002/(sici)1520-6777(1999)18:5<511::aid-nau14>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pregnancy and contractile activity on bladder muscarinic receptor subtypes

Abstract: In the rabbit bladder, pregnancy and prolonged bladder contractions decrease both muscarinic receptor density and contractile response, whereas newborns show enhanced muscarinic contractile response. Although the M 2 receptor predominates in rabbit bladder, we and others have shown that the affinity of a series of subtype selective muscarinic antagonists for inhibition of muscarinic agonist-induced contractions is most consistent with the pharmacologically defined M 3 receptor directly mediating smooth muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Studies in rats, rabbits, and guinea pigs have shown that the increased estrogen and progesterone levels during pregnancy generate bladder hypertrophy and increase capacity, possibly through degenerative and regenerative changes in the autonomic innervation of the lower urinary tract [Owman, 1981;Batra and Andersson, 1989;Qayyum et al, 1989;Lee et al, 1993;Hsia and Shortli¡e 1995;Tong et al, 1995;Baselli et al, 1999;Grandadam et al, 1999].…”
Section: E¡erent Autonomic Nerve Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in rats, rabbits, and guinea pigs have shown that the increased estrogen and progesterone levels during pregnancy generate bladder hypertrophy and increase capacity, possibly through degenerative and regenerative changes in the autonomic innervation of the lower urinary tract [Owman, 1981;Batra and Andersson, 1989;Qayyum et al, 1989;Lee et al, 1993;Hsia and Shortli¡e 1995;Tong et al, 1995;Baselli et al, 1999;Grandadam et al, 1999].…”
Section: E¡erent Autonomic Nerve Functionmentioning
confidence: 99%
“…Postganglionic nerve endings innervate the smooth muscle of the bladder and urethra in humans [Gosling et al, 1998] and possibly the striated rhabdosphincter in animals [Elbadawi and Schenk, 1974]. Transmission in the bladder ganglia is mainly mediated via nicotinic receptors (acetylcholine release), whereas postganglionic transmission occurs mainly via di¡erent muscarinic receptor subtypes (acetylcholine release) [deGroat, 1976;Baselli et al, 1999].…”
Section: E¡erent Nerve Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,5,11,14,16,25,26 Various studies have shown that the maximum cystometric capacity is significantly increased in pregnancy with decreased voided urine volumes and that the bladder muscarinic receptor density is reduced with a consequent and marked decrease in cholinergic contractile response and a relative increase in the purinergic component. 4,10,25 The decreased bladder contractility was traditionally believed to be a non-specific response to uterine quiescence in pregnancy secondary to the close anatomical relationship between the two organs. More recently, this was considered as an abnormal detrusor reaction to first-trimester hormonal changes similar to hyperemesis gravidarum.…”
Section: Discussionmentioning
confidence: 99%
“…3,[5][6][7][8] Experimental and clinical studies have shown that pregnancy induces substantial changes in the urinary bladder resulting in decreased contractility and suggest that the specific hormonal changes during pregnancy may be primarily responsible. 1,2,4,5,9,10 Estrogen, progesterone and relaxin are implicated for their ability to influence the function of the urinary bladder. [1][2][3][4][5]7,9,[11][12][13][14] However, relatively little information exists to support a clear association between hormonal levels and lower urinary tract symptomatology in longitudinal studies of pregnant women.…”
Section: Introductionmentioning
confidence: 99%